Pengaruh adverse childhood experiences terhadap kecemasan pada siswa SMA di Kota Banda Aceh - Novita, Novita; Abdullah, Asnawi; Marthoenis, Marthoenis (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Adolescent mental health is a strategic issue in public health development in Indonesia. One factor proven to have a strong association with anxiety disorders is adverse childhood experiences (ACEs). ACEs are negative experiences experienced by someone in childhood before the age of 18. This issue is important to address in educational settings because it can impact students' mental and academic well-being. Purpose: To analyze the influence of adverse childhood experiences on anxiety in high school students. Method: This quantitative study, with a cross-sectional design, was conducted from January to February 2025 in Banda Aceh City, with high school students as subjects. The sample was selected using stratified random sampling, resulting in 310 respondents. Data were analyzed using univariate and bivariate Chi-square tests. Results: Statistical analysis showed that ACEs had the most dominant influence on student anxiety (OR=52.16; 95% CI=9.22–295.24; p=0.0001). Other related factors were school environment (OR=4.28; p=0.0001), academic load (OR=2.24; p=0.012), and coping strategies (OR=2.22; p=0.0001). Multivariate analysis showed that individuals with high-risk adverse childhood experiences (ACEs) and family adaptation had a 35-fold higher risk of experiencing panic-level anxiety (pseudo-R2=0.1544), while individuals with a moderately supportive school environment had a 21-fold higher risk of experiencing panic-level anxiety (pseudo-R2=0.2191). Conclusion: Adverse childhood experiences (ACEs) were significantly associated with anxiety levels in high school students. The most dominant factor associated with student anxiety was high-risk ACEs, followed by a less supportive school environment and ineffective coping strategies. Suggestion: The results of this study are expected to be the basis for formulating promotive and preventive policies for adolescent mental health in the school environment, as well as being a reference for local governments and educational institutions in developing school-based counseling and psychosocial intervention programs. Keywords: Adverse Childhood Experiences; Anxiety; High School Students; Mental Health. Pendahuluan: Kesehatan mental remaja merupakan salah satu isu strategis dalam pembangunan kesehatan masyarakat Indonesia. Salah satu faktor yang terbukti memiliki hubungan kuat dengan gangguan kecemasan adalah adverse childhood experiences (ACEs). ACEs merupakan pengalaman negatif yang dialami seseorang di masa kanak-kanak sebelum usia 18 tahun. Masalah ini penting ditangani di lingkungan pendidikan karena dapat memengaruhi kesejahteraan mental dan akademik siswa. Tujuan: Untuk menganalisis pengaruh adverse childhood experiences terhadap kecemasan pada siswa SMA. Metode: Penelitian kuantitatif dengan desain cross-sectional, dilakukan pada bulan Januari-Februari 2025 di wilayah Kota Banda Aceh dengan subjek penelitian siswa SMA. Sampel dipilih dengan stratified random sampling dan mendapatkan 310 responden. Analisis data menggunakan univariate dan bivariat Chi-square. Hasil: Analisis statistik menunjukkan bahwa ACEs memiliki pengaruh paling dominan terhadap kecemasan siswa (OR=52.16; 95% CI=9.22–295.24; p=0.0001). Faktor lain yang berhubungan adalah lingkungan sekolah (OR=4.28; p=0.0001), beban akademik (OR=2.24; p=0.012), dan strategi coping (OR=2.22; p=0.0001). Berdasarkan analisis multivariat menunjukkan bahwa pada adaptasi diri dan keluarga adverse childhood experiences (ACEs) risiko tinggi berpeluang 35 kali mengalami kecemasan tingkat panik (nilai pseudo R2=0.1544), sedangkan adaptasi lingkungan sekolah yang cukup mendukung berpeluang 21 kali mengalami kecemasan tingkat panik (nilai pseudo R2=0.2191). Simpulan: Adverse Childhood Experiences (ACEs) memiliki hubungan yang signifikan dengan tingkat kecemasan pada siswa SMA. Faktor yang paling dominan berhubungan dengan kecemasan siswa adalah ACEs risiko tinggi, diikuti oleh lingkungan sekolah yang kurang mendukung serta strategi coping yang tidak efektif. Saran: Diharapkan hasil penelitian ini dapat menjadi dasar dalam penyusunan kebijakan promotif dan preventif kesehatan mental remaja di lingkungan sekolah, serta menjadi rujukan bagi pemerintah daerah dan instansi pendidikan dalam mengembangkan program konseling dan intervensi psikososial berbasis sekolah. Kata Kunci: Adverse Childhood Experiences; Kecemasan; Kesehatan Mental; Siswa.